2003
DOI: 10.1078/0944-5013-00211
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of a phytopathogenic fungus, Colletotrichum species by acetic acid

Abstract: Acetic, oxalic, malic, and citric acids significantly inhibited the growth of Colletotrichurm, gloeosporioides, a phytopathogenic fungus, and acetic acid showed the strongest inhibition with no growth at 50 mM. The growth inhibition by these organic acids was closely related with the inhibition of respiration, as tested using three species, C. gloeosporioides, C. coccodes, and C. dermatium. Optimum growth of C. gloeosporioides was observed around pH 6.0. The inhibition of growth by acetic acid accelerated alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 17 publications
2
51
0
2
Order By: Relevance
“…This indicates that acetic acid successfully inhibited the infection on strawberry fruit. It has been reported that organic acids and their salts alone on or in combination inhibit the growth of bacteria and fungi [4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that acetic acid successfully inhibited the infection on strawberry fruit. It has been reported that organic acids and their salts alone on or in combination inhibit the growth of bacteria and fungi [4].…”
Section: Resultsmentioning
confidence: 99%
“…The optimal growth of Colletotrichum species has been observed at pH 6.0 and the inhibition of growth by acetic acid has been accelerated and linked with a decrease in pH from 6.0 to 4.0 [4]. Several researchers thus propose to control Colletotrichum infection by using acetic acid, which is generally less dangerous than fungicides [4]. Considering the inhibitory role of organic acids, some mechanisms of pathogen repression have been suggested, including membrane disruption with sorbic acid [5] and the interruption of metabolic reactions with benzoate [6].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Inhibition of Chlorella growth during heterotrophic cultivation increased with the increase in the neutralized citrate buffer loading from 0.5% to 10%, although further loading increases (15%, 20%) did not alter inhibition rate, which remained as for a 10% loading. Citrate buffer contains citric acid, which has been reported to be inhibitory to bacteria [20] and fungi [21]. Citric acid has also been reported to exert positive [22] or negative [23] effects on Chlorella growth.…”
Section: Effect Of Neutralized Citrate Buffer On Chlorella Growthmentioning
confidence: 99%